Dose-inhibition curve and its application to the analysis of ACh-receptor activity - Matsumoto, M; Sasaki, K; Somei, K; Sato, M (Japanese journal of physiology, 1980)
Most of the classical studies on the mode of inhibition by various inhibitors specific to the postsynaptic receptors have been done by observing dose-response curves with a parameter of inhibitor concentration. The aim of this paper is to describe a new method we derived from conventional enzyme kinetics and to examine the applicability of this method to practical experiments for analyzing receptor-inhibitor interactions. The relative change in agonist-induced response in the presence of the inhibitor was plotted against inhibitor concentration in logarithmic scale. This curve may be called a dose-inhibition curve with a agonist concentration parameter. Our theory makes the following predictions: (1) If the curve shifts to the right with the increase in agonist concentration, the mode of inhibition should be competitive; (2) If the curve shifts to the left with the increase in agonist concentration, the mode of inhibition should be uncompetitive; (3) If the curve remains unchanged with the change in agonist concentration, the mode of inhibition should be noncompetitive. In order to examine the applicability of this method, we chose the excitatory type of acetylcholine-induced responses of the ganglion cells in Aplysia, and analyzed the mode of inhibition by decamethonium (Deca) and tetraethylammonium (TEA). This type of analysis suggested that the mode of inhibition by Deca was competitive whereas that by TEA was noncompetitive.